Artikel Review: Kesesuaian Pengelolaan Limbah Obat dan Medis dengan Pedoman Nasional pada Berbagai Tingkat Pelayanan Kesehatan - Gabryuvela Gabryuvela; Laohannia Challiztha; Noor Latifah (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
The management of pharmaceutical and medical waste, particularly expired or damaged drugs, remains a challenge across various healthcare facilities. A study at Grade II R. W. Mongisidi Hospital in Manado showed a 76% compliance rate with the Ministry of Health’s 2021 guidelines, while Mamuju Regional Hospital failed to meet the standards outlined in Regulation No. 1204/2004. In community pharmacies in East Bandung, most facilities disposed of drugs independently, with only 59.6% following proper waste management procedures. These findings highlight the need for improved supervision, education, and adherence to standardized guidelines to minimize the negative impacts on health and the environment.